2017
DOI: 10.1007/s11274-017-2282-x
|View full text |Cite
|
Sign up to set email alerts
|

Mini-review: high rate algal ponds, flexible systems for sustainable wastewater treatment

Abstract: Over the last 20 years, there has been a growing requirement by governments around the world for organisations to adopt more sustainable practices. Wastewater treatment is no exception, with many currently used systems requiring large capital investment, land area and power consumption. High rate algal ponds offer a sustainable, efficient and lower cost option to the systems currently in use. They are shallow, mixed lagoon based systems, which aim to maximise wastewater treatment by creating optimal conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 75 publications
6
48
0
1
Order By: Relevance
“…The observed variation in the daily flows was due to the fluctuations in the population of the township and was not subject to a regular, predictable pattern. The mean daily flow was 12 m 3 , consistent with the long-term average. The daily inflow comes from a central pumping station in the township, which is activated and deactivated by float switches.…”
Section: Wastewater Treatment Plant Sitesupporting
confidence: 77%
See 2 more Smart Citations
“…The observed variation in the daily flows was due to the fluctuations in the population of the township and was not subject to a regular, predictable pattern. The mean daily flow was 12 m 3 , consistent with the long-term average. The daily inflow comes from a central pumping station in the township, which is activated and deactivated by float switches.…”
Section: Wastewater Treatment Plant Sitesupporting
confidence: 77%
“…The mean BOD 5 removal from the inlet wastewater following treatment in HRAP1 was consistent with that reported for longitudinal studies on the same pond, 91.76% and 93.4%, 1,23 and similar to removal rates reported for other HRAPs treating domestic wastewater. 3 Following treatment in HRAP2, the mean BOD 5 concentration at the outlet of HRAP2 was 23.85 ± 10.92 mg BOD 5 L −1 , higher than the HRAP2 inlet water supplied from HRAP1 and independent-samples Mann-Whitney U test showed that this difference was statistically significant (p = 0.007; n = 40). The most likely reason for the increased BOD 5 concentration in HRAP2 is that the ageing biomass in the pond was degrading and releasing extracellular material into suspension, increasing the organic matter concentration.…”
Section: Wastewater Characteristics During the Validation Periodmentioning
confidence: 85%
See 1 more Smart Citation
“…Pond systems are common in bacterial WWT . They are also the most widely applied type of large‐scale reactor for microalgae cultivation, because of their simple construction and low investment costs .…”
Section: (Photo‐)bioreactor Systems For Algae‐based Wwtmentioning
confidence: 99%
“…Solar radiation is the primary form of energy for microalgae, as they are photosynthetic organisms . Most algae have an optimal solar radiation range in which they prefer to grow, and the shallow design of HRAPs maximises the amount of light for algal growth (Young et al 2017). Regular harvesting and mixing can help minimise self-shading that occurs at high concentrations.…”
Section: Introductionmentioning
confidence: 99%